Bolivia frente al conflicto en Gaza: su voz por la cuestión de Palestina - Ceppi, Natalia Paola (El Colegio de México A.C., 2024)
The attack perpetrated by Hamas against Israel on October 7, 2023, and the consequent Israeli offensive marked the beginning of a new chapter in the extensive and complex history of the conflict in Gaza. However, unlike other escalations of violence, this one is not–nor will it be–just another one. Latin American voices are distinguished by their diverse stances. In this context, Bolivia clearly identifies with one of the causes. On various occasions, it has reaffirmed its unconditional support for a just and lasting solution to the conflict in Gaza that allows the Palestinian people to exercise the right to self-determination and have an independent and sovereign state with borders prior to 1967, with East Jerusalem as its capital.